Induction of Antioxidant Capacity and Hydroxymethylfurfural Content Variations by Modifications of Cooked Fruit Processing. - Kevers Claire; Brack François; Pincemail Joël; Michel Cloes Jean; Dommes Jacques (Journal of Antioxidant Activity, 2015)
Liège syrup is a Belgian traditional cooked fruit foodstuff, produced mainly from apples and pears. The process includes several hours of heating at high temperature during which complex chemical reactions occur, such as Maillard condensation between reducing sugars and amino acids. Aiming at understanding the modifications of the fruit juices during heating, different parameters were monitored throughout the process. It was shown that hydoxymethylfurfural was formed during the first step of concentration by heating. At the end of the process, hydroxymethylfurfural had totally disappeared and the deep brown color of the product suggested that this compound was transformed into melanoidins. A parallel increase in antioxidant capacity was also observed. To determine optimal conditions to reach high melanoidin content and high antioxidant capacity, different in vitro model systems were compared. It was shown that different combinations of an amino acid with glucose or fructose led to different levels of hydroxymethyfurfural, of melanoidins and antioxidant capacity. After heating of apple or pear puree, an increase of the antioxidant capacity and the hydroxymethylfurfural and melanoidin contents was observed when the heating time was doubled. An increase of the pH from 5 to 9 in apple marmalade’s also induced an increase in antioxidant capacity and in hydroxymethylfurfural and melanoidins. However it was not the case in pear marmalade where only the increase in antioxidant capacity was observed. These results suggest that some parameters of the processing could be modified to improve the health-promoting effect of this traditional food (antioxidant properties and composition in hydroxymethylfurfural and melanoidins). The main factors affecting the quality of the final product were the cooking times, the temperature, the pH, the addition of reducing sugars or amino acids.
Keywords: Liège syrup